Analysis of the Problems of Police Shooting on Sight Cases from a Criminal Law Perspective - Janintra Pasha Maheswara; Muchammad Iksan (Universitas Muhammadiyah Surakarta, 2023)
The purpose of the research in this research is to find out how the Police are authorized to use firearms and know the procedures for imposing sanctions on members of the Police who violate the SOP of shooting on the spot. Research uses normative legal research, namely research on legal rules, principles, concepts or doctrines. Involves careful systematic exposition, analysis, and critical evaluation of legal rules, principles or doctrines. the authority to use firearms comes from the subjective self of the police officers, who have the freedom to do or not do anything at their own discretion. As a result, discretion cannot be separated from the power or authority attached to officials to act freely with due regard and responsibility for those actions. From the provisions regarding criminal law related to murder in Article 338 of the Criminal Code if the police violate the SOP, in which murder is punishable by a prison sentence of 15 years in prison (more than 4 years), then of course a general court process must be carried out before the trial of the National Police code of ethics commission.